Evaluation of the association between osteoporosis and periodontitis in postmenopausal women: A clinical and radiographic study - Saba Zamani; Farin Kiany; Leila Khojastepour; Ali Zamani; Zahra Emami (Wolters Kluwer Medknow Publications, 2022)
Background: This study aimed to assess the relationship between the osteoporotic condition and periodontitis in postmenopausal women. Materials and Methods: Ninety-four women aged 50-80 years were studied in this cross-sectional study. Bone mineral density (BMD) of lumbar vertebra BMD (LBMD), total hip BMD (HBMD), and neck of femur BMD (NBMD) was assessed using standardized dual-energy X-ray absorptiometry (DXA) (normal: T-score ≥−1, osteopenic: −2.5 ≤ t-score <−1, osteoporotic: T-score <−2.5). Bleeding point index (BI), O'Leary plaque index (PI), and clinical attachment loss (CAL) were recorded. Cementoenamel junction, alveolar-crest distance (CEJ-AC) was measured from cone-beam computed tomography images. Periodontitis severity was represented by CAL and CEJ-AC distance. One-way analysis of variance followed by Post hoc Tukey was performed for examining differences among the groups for different variables. Pearson correlation coefficient® and backward regression analysis were used to investigate the effect of confounding variables on CEJ-AC as the dependent variable. Significance was considered at P < 0.05. Results: Mean CEJ-AC was significantly higher in the osteoporotic and osteopenic groups compared to the normal group (P = 0.001). There was a significant positive correlation between CEJ-AC and NBMD and LBMD (P < 0.001). The associations between LBMD and CEJ-AC existed even after adjusting for confounding factors (P = 0.002). The differences in BI, PI, and CAL were not statistically different between the groups (P > 0.05). Conclusion: Although osteoporosis is not the main cause of periodontitis, it can indirectly affect periodontal status by increasing CEJ-AC. Early diagnosis of osteoporosis followed by early referral to a dentist for the treatment of potential existing periodontal diseases is important to avoid complications among postmenopausal women